2015
DOI: 10.1523/jneurosci.2053-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-33 Regulates ApoE Lipidation and Amyloid-β Metabolism in the Brain

Abstract: Dysregulation of amyloid-␤ (A␤) metabolism is critical for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 41 publications
3
71
0
Order By: Relevance
“…After 48 hours, the levels of miR-155, miR-233, and miR-33 were upregulated and miR-433 was downregulated in response to Ab (represented by solid lines). The targeted genes of the miRNAs and their involved pathways (represented by dashed lines) were supported by the following studies: 1) Xu et al 47 ; 2) Lukiw et al 46 ; 3) Qadir et al 48 ; 4) Kim et al 19 These target genes were confirmed in the neuroretina or RPE/choroid with same tendency in our study. IV, intravitreal injection.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…After 48 hours, the levels of miR-155, miR-233, and miR-33 were upregulated and miR-433 was downregulated in response to Ab (represented by solid lines). The targeted genes of the miRNAs and their involved pathways (represented by dashed lines) were supported by the following studies: 1) Xu et al 47 ; 2) Lukiw et al 46 ; 3) Qadir et al 48 ; 4) Kim et al 19 These target genes were confirmed in the neuroretina or RPE/choroid with same tendency in our study. IV, intravitreal injection.…”
Section: Discussionsupporting
confidence: 89%
“…It has been clearly reported that miR-33 regulates ABCA1 and Ab levels in the brain. 19 MicroR-33 could reduce the expression of the ABCA1 gene by binding to the 3 0 UTR of ABCA1. ABCA1 has a positive effect on ApoE lipidation and an inhibitory effect on Ab levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with the RXR agonist bexarotene also improves Aβ clearance and cognition [106], in a manner dependent on the presence of both APOE [106] and ABCA1 [107]. Other treatments to improve apoE4 lipidation (e.g., microRNA-33 induction [108], retinoic acid [109]) could prove useful in preventing brain phenotypes associated with APOE4 and neurodegeneration.…”
Section: Mechanisms Of Effects Of Apoe Genotype Effectsmentioning
confidence: 99%
“…to dementia, the presence of the APOE ε4 allele is associated with more rapid brain volume deficits and cortical thinning over time, as shown in several longitudinal MRI studies (85)(86)(87).…”
Section: Discussionmentioning
confidence: 83%